Differences Between Schools of Choice and Traditional Comprehensive Schools in Their Grade 9 Academic Performance - Browne, Divina; Slate, John R (International Journal of Social Learning (IJSL), 2021)
This study was conducted to determine the differences between schools of choice and traditional comprehensive high schools in terms of their Grade 9 State of Texas Assessments of Academic Readiness (STAAR) End-of-Course (EOC) exams in Biology, English 1, and Algebra 1 during the 2017-2018 school year. Inferential statistical analyses revealed the presence of a statistically significant difference between the two types of schools on their EOC exam passing rates in all three content areas for students who were not at-risk and for students who were not in poverty. In contrast, statistically significant differences were not revealed between the two types of schools in terms of the EOC exam passing rates of their CATE and Non-CATE students. Knowing that students who have choice appear to perform better academically, policymakers are encouraged to study the feasibility of channeling more funding to help school districts expand their school choice programs to (a) motivate more students to find the school that fit their needs and their future college and career aspirations, and (b) to solicit more support from parents and community businesses to invest in their communities to improve schools through taxes. Given that the data for this research were gathered for only 16 school districts in South Texas, researchers are encouraged to conduct a study that will involve all school districts in the whole state and possibly the whole nation to reach more conclusive evidence on the differences between schools of choice and neighborhood schools.